Wideband Decoupling Circuit for Sub-6 GHz Co-Polarized In-Band Full-Duplex Patch Antennas - Zhang, Yi-Ming; Zheng, Shao-Yong (IEEE transactions on antennas and propagation, 2025)
To minimize the mutual coupling between co-polarized aperture-coupled patch antennas used in full-duplex applications, a novel decoupling method is introduced. This method involves creating an additional transmission bridge between the apertures of the two antenna elements at the feeding layer, effectively canceling the mutual coupling at the center frequency. The transmission bridge comprises two key components, which are a coupling structure connecting the aperture to a fork-shaped branch line, and a cancellation circuit. Notably, the cancellation circuit boasts wideband magnitude and phase compensation capabilities, providing a broadband decoupling response. Furthermore, it does not require any additional impedance-matching structures. To demonstrate the effectiveness, a 1× 2 co-polarized patch antenna array operating at 5.0 GHz was designed, fabricated, and tested. The measured port-to-port isolation of the array exceeded 50 dB, with a fractional bandwidth of 14.0%. Despite the use of lossy resistors, the insertion loss is less than 0.88 dB. These results underscore the advantages of the proposed coupling cancellation method, which offers a wide bandwidth, a low profile, and a straightforward design process.